The Fundraising Strategy in Empowerment Society Program (Case Study "Receiving Alms Program for Used Cooking Oil for Them” At Kutub Social House - South Jakarta) - Stafhanie Dumas; Muhammad Sahrul; Sokhivah Sokhivah; Endang Rudiatin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Fundraising is the main activity of a company or institution, especially a non-profit organization that relies more on its funds for fundraising. Therefore, a good strategy is necessary to carry out this fundraising activity for the institution's survival. This study aims to determine how the fundraising strategy in the Community Empowerment program. This field research uses a qualitative method with a descriptive approach and analyzes the data obtained from interviews, observations, and documentation. Data analysis was done through data presentation, data reduction, and conclusion. The research location is the Kutub Social House Institute, South Jakarta. The results showed that the Kutub Social House institution in the "Receiving Alms Program for Used Cooking Oil for Them" used the Fundraising method, namely Face To face, direct socialization to the community, and Campaign, namely by carrying out promotions to collect used cooking oil through communication media such as the internet, official websites, and the IG of the Kutub Social House. From the fundraising method Kutub Social House, the community is interested in the "Receiving Alms Program for Used Cooking Oil for Them," The community can collect used cooking oil. The used cooking oil collected from the community will be exported, and the export proceeds of used cooking oil, in the form of alms funds for operations in support of community empowerment programs in the Kutub Social House and empowerment programs in each region that participates in the the "Receiving Alms Program for Used Cooking Oil for Them." Types of utilization programs include essential material assistance, cooking oil, compensation for orphans, compensation for the poor, compensation for the elderly, and assistance for nutritional intake for children whose body weight is below the red line.